Some Powerful Techniques for Solving Nonlinear Volterra-Fredholm Integral Equations - Hamoud, Ahmed A.; Mohammed, Nedal M.; Ghadle, Kirtiwant P. (Journal of Applied Nonlinear Dynamics, 2026)
The main object of the present paper is to study the behavior of the approximated solutions of the nonlinear mixed Volterra-Fredholm integral equations by using Adomian Decomposition Method (ADM), Modified Adomian Decomposition Method (MADM), Variational Iteration Method (VIM) and Homotopy Analysis Method (HAM). Moreover, we discuss some new uniqueness results. Finally, some examples are included to demonstrate the validity and applicability of the proposed techniques.